1997
DOI: 10.1046/j.1365-2648.1997.1997025163.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment in nursing

Abstract: Sexual harassment is a problem faced by women in the workplace which can lead to adverse psychological consequences as well as impaired work performance. Sexual harassment is about the abuse of power and status rather then merely being about sex per se and has to be viewed in the context of institutionalized male power. Although there is a relative dearth of research, there is increasing evidence that sexual harassment of nurses is common and that it can have adverse effects on nurses physical and psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 20 publications
3
37
0
1
Order By: Relevance
“…The respondents in this study who revealed that they had been sexually harassed, indicated that when their work performance was effected, it was most commonly due to decreased concentration, which corresponds with the finding of Robbins, Bender and Finnis (1997). Kumalo (1998) states that occupational work accidents happen when the relevant person is not concentrating fully on the job at hand.…”
Section: Total Number Of Responses = 147supporting
confidence: 66%
See 2 more Smart Citations
“…The respondents in this study who revealed that they had been sexually harassed, indicated that when their work performance was effected, it was most commonly due to decreased concentration, which corresponds with the finding of Robbins, Bender and Finnis (1997). Kumalo (1998) states that occupational work accidents happen when the relevant person is not concentrating fully on the job at hand.…”
Section: Total Number Of Responses = 147supporting
confidence: 66%
“…The victims in the studies conducted by Assey and Herbert (1983), Gutek and Koss (1993), Robbins, Bender and Finnis (1997), Weerakoon and O'Sullivan (1998) also reported experiencing these emotions.…”
Section: Total Number Of Responses = 147mentioning
confidence: 90%
See 1 more Smart Citation
“…However, this type of violence is known to be under reported, as it is a sensitive subject that is considered taboo, and the victim is at risk to be stigmatized. [24] Some studies have noted that exposure to sexual violence among nurses is as high as 7%-76%. [10,24] In the present study, only 4.1% reported exposure to sexual violence.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Some studies have noted that exposure to sexual violence among nurses is as high as 7%-76%. [10,24] In the present study, only 4.1% reported exposure to sexual violence. This low number may be because the nurses did not report the incidents due to the risk of being stigmatized.…”
Section: Discussionmentioning
confidence: 99%